2009
DOI: 10.1097/shk.0b013e3181a53842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Trem 1 Pathway Modulation During Hemorrhagic Shock in Rats

Abstract: The triggering receptor expressed on myeloid cells (TREM) 1, a receptor expressed on the surface of neutrophils and monocytes/macrophages, synergizes with the Toll-like receptors in amplifying the inflammatory response mediated by microbial components. Because the pathogenesis of severe blood loss-induced excessive inflammation and multiple organ failure implies leukocyte activation and bacterial translocation, we hypothesized that the TREM-1 pathway modulation would prove beneficial in this setting. Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Several studies have shown that treatment with TREM-1 inhibitors represents a therapeutic strategy to prevent excessive inflammation resulting in decreased pathology and mortality. The inhibitory peptide LP17 was shown to successfully reduce the inflammatory responses in the context of infection, mesenteric IR-induced injury, hemorrhagic shock, colitis, autoimmune arthritis and acute pancreatitis1220343536373839. In addition, TREM-1 fusion protein and LR12 reduced the disease severity in sepsis and in models of acute myocardial infarction132324404142.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that treatment with TREM-1 inhibitors represents a therapeutic strategy to prevent excessive inflammation resulting in decreased pathology and mortality. The inhibitory peptide LP17 was shown to successfully reduce the inflammatory responses in the context of infection, mesenteric IR-induced injury, hemorrhagic shock, colitis, autoimmune arthritis and acute pancreatitis1220343536373839. In addition, TREM-1 fusion protein and LR12 reduced the disease severity in sepsis and in models of acute myocardial infarction132324404142.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of HS, the TREM-1 modulation by LP17 attenuated the haemodynamic compromise, the development of lactic acidosis, prevented form cytokine production, organ dysfunction and finally improved survival. 49 Ischemia-reperfusion. Acute mesenteric ischemia is a medicosurgical emergency associated with 60 to 90% mortality.…”
Section: Trem-1 Structure and Functionmentioning
confidence: 99%
“…1A) [13, 15, 2324]. While the natural TREM-1 ligand is not yet known, based on a new model of immune signaling, the signaling chain homooligomerization (SCHOOL) model [25], we have developed a novel, ligand-independent approach to TREM-1 inhibition (Fig.…”
Section: Introductionmentioning
confidence: 99%